Psychiatry Trainees' Attitudes, Knowledge, and Training in Addiction Psychiatry—A European Survey - Orsolini, Laura; Rojnić Palavra, Irena; Papanti, Gabriele Duccio; Potočan, Matej; Quattrone, Diego; Martens, Matis; Sklenářová, Sandra; Levola, Jonna; Grichy, Leslie; Naughton, Sean; Grinevičiene, Indre Kotryna; Kuiters, Jelly Petra; et al. (Frontiers in Psychiatry, 2021)
Background: Although psychoactive substance use disorders (PSUDs) are a domain of mental health, addiction psychiatry is only formally recognized as a subspecialty in a few European countries, and there is no standardized training curriculum. Methods: A 76-item questionnaire was developed and disseminated through an online anonymous data-collecting system and hand-to-hand amongst psychiatric trainees from the 47 European countries of the Council of Europe plus Israel and Belarus. Results: 1,049/1,118 psychiatric trainees from 30 European countries completed the questionnaire. Fifty-nine-point nine percent of trainees stated to have training in addictions. Amongst the trainees who described having training in addictions, 43% documented a not well-structured training and 37% an unsatisfactory training, mainly due to poor acquired knowledge. Overall, 97% of trainees stated that addiction represents a core curriculum for their training. Overall, general adult psychiatric trainees reported a better knowledge in addictions, compared to trainees in child and adolescent psychiatry. Conclusion: Despite a growing spread of PSUDs in European countries, addiction psychiatry is a relatively poorly trained field within psychiatry training programs. Further research should investigate reasons for poor training and timings of the educational activities to optimize experiential education training in addiction psychiatry.